La libéralisation des marchés de l´électricité et du gaz naturel au niveau européen – enjeux et défis actuels - Irina Maria Găman (Romanian Journal of European Affairs, 2010)
The creation of an internal energy market at the European level becomes nowadays a sine qua non condition for a single and coherent voice on energy issues at the global level for the EU. One essential step to be done is the liberalization of energy sectors, such as electricity and natural gas. This process of liberalization for the electricity and gas market should have been totally and homogeneously accomplished by the mid of 2007 by the member states of the EU, goal established by the European Commission through two legal instruments, more precisely the Directive 2003/54/EC and the Directive 2003/55/EC. Despite the European legislative settlement and despite the existence of common institutions of regularization, the liberalization has its limits. How these limits can be explained and which are the factors for the heterogeneous degree of liberalization of the electricity and gas markets at the European level? This article is focusing on the specific economic and political factors through which the limits of liberalization of energy markets can be explained.